Sparking a worldwide energy revolution : social struggles in the transition to a post-petrol world - Abramsky, Kolya (AK Press, 2010)
There are no technofixes. Neither 'clean' energy nor 'green' capitalism will preserve our lands, rivers, oceans, health, and lives. Neither governments nor corporations nor 'the market' can bring us out of the netherworld they themselves have created. Mother Earth calls to the grass-roots for entirely new social relations, human and less hellish. This sober and serious book heeds that call."ùPeter Linebaugh, author of The Magna Carta Manifesto: Liberties and Commons for All.